Creative activities for young children - Mayesky, Mary (Wadsworth Cengage Learning, 2012)
"Creative Activities for Young Children, 10th Edition, is a terrific book filled with fun, creative, and easy-to implement activities for young children. You'll be encouraged to exercise your own creativity, as well as learn how to help young children do the same. Hundreds of activities, up-to-date research, recipes, finger plays, information on how to select children's books, and more make this book an invaluable resource for you and others planning to work creatively with children across the curriculum--and one you'll want to keep for use throughout your professional career."